Combination of Antifungal Drugs and Protease Inhibitors Prevent Candida albicans Biofilm Formation and Disrupt Mature Biofilms - Lohse, Matthew B.; Gulati, Megha; Craik, Charles S.; Johnson, Alexander D.; Nobile, Clarissa J. (Frontiers in Microbiology, 2020)
Biofilms formed by the fungal pathogen Candida albicans are resistant to many of the antifungal agents commonly used in the clinic. Previous reports suggest that protease inhibitors, specifically inhibitors of aspartyl proteases, could be effective antibiofilm agents. We screened three protease inhibitor libraries, containing a total of 80 compounds for the abilities to prevent C. albicans biofilm formation and to disrupt mature biofilms. The compounds were screened individually and in the presence of subinhibitory concentrations of the most commonly prescribed antifungal agents for Candida infections: fluconazole, amphotericin B, or caspofungin. Although few of the compounds affected biofilms on their own, seven aspartyl protease inhibitors inhibited biofilm formation when combined with amphotericin B or caspofungin. Furthermore, nine aspartyl protease inhibitors disrupted mature biofilms when combined with caspofungin. These results suggest that the combination of standard antifungal agents together with specific protease inhibitors may be useful in the prevention and treatment of C. albicans biofilm infections.